Effects of cognitive behaviour therapy and acceptance and commitment therapy on depression, anxiety, and quality of life among emerging adults in Selangor, Malaysia - Ahmad Othman, Akmarina (2022)
Adults between 18 and 29 years old experience more mental health problems, such as depression (a major local and global public health issue) compared to other age populations. Despite the safety and efficacy of cognitive behaviour therapy (CBT), comparisons between CBT and the newer acceptance and commitment therapy (ACT) among emerging adults in Malaysia remain scarce. Most local and global works generally emphasised university or college students rather than emerging adults in general, hence creating a population gap in current literature. Consequently, this study compared the CBT and ACT effects on emerging adults’ depression and anxiety symptoms and quality of life. This study utilised an experimental design with a pre-test, post-test, and three-month follow-up. Specifically, 102 emerging adults between 18 and 29 years old who fulfilled the inclusion criteria were recruited from two study locations in Selangor, Malaysia and randomly stratified into two experimental groups (CBT and ACT) and one control group. The experimental groups underwent CBT or ACT, whereas the control group received psychoeducation. As the data collection tools employed in this study, Beck Depression Inventory-II (BDI-II), Beck Anxiety Inventory (BAI), and The World Health Organization Quality of Life: Brief Version (WHOQL-BREF) were completed thrice by the participants. Notably, 81 participants completed the study until the follow-up stage. The elicited data were analysed using one-way ANOVA, Kruskal-Wallis test, The CBT demonstrated a significant difference in depression, anxiety, total quality of life, and its four domains post-test, thus implying significant improvement post-intervention. Regardless, the absence of a significant difference during follow-up indicated score maintenance. The ACT, which denoted a significant difference in anxiety scores and both physical and psychological domains at post-test and follow-up, implied a significant improvement post-treatment and during the follow-up. In terms of depression, total quality of life, social relationship, and environment domain, the ACT showed a significant difference post-test, albeit with no significant difference during the follow-up. The aforementioned outcomes imply the ACT is effective in reducing depression symptoms compared to the control group. Despite being nonsignificant, the CBT demonstrated a higher reduction in depression scores post-test compared to the control group. The CBT continues to reflect improvement in depression at follow-up compared to the control. Both CBT and ACT denoted a similar effectiveness post-test with regards to anxiety and quality of life. Notwithstanding, ACT proved more effective to lower anxiety and to increase physical, and psychological health at follow-up compared to CBT. The current study findings complemented both CBT and ACT effectiveness in terms of reducing depression and anxiety symptoms and improving the quality of life among emerging adults in Malaysia. Furthermore, the ACT appeared more effective in depression, anxiety, and physical and psychological domains compared to CBT. These results would benefit emerging adults between 18 and 29 years old and counsellors or mental health professionals who frequently manage emerging adults with depression and aspects involving quality of life. Future works should test a longer period of follow-up and perform similar studies at different locations as emerging adulthood (EA) is culture-specific.